Empowering Young Learners: Insights into EFL Teachers’ Perceptions and Practices within the IB Framework in Elementary School - Chaerunnisa, Alifia; Bachtiar, Bachtiar; Ruminda, Ruminda (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
Drawing from the theoretical perspective that effective English as a Foreign Language (EFL) instruction requires integration with contemporary educational frameworks, this study explores how the International Baccalaureate (IB) framework shapes EFL teachers' perceptions and practices in an elementary school in Tangerang, Indonesia. The research aims to examine the impact of IB principles on teaching methodologies and the resultant educational outcomes for young learners. Utilizing a qualitative narrative inquiry approach, six EFL teachers were interviewed and observed, and their teaching materials were analyzed to provide a comprehensive understanding of their experiences and instructional strategies. The findings reveal that teachers adopt student-centered, inquiry-based methods that foster critical thinking, global awareness, and practical language skills. This integration enhances student engagement and learning outcomes, highlighting the effectiveness of the IB framework in promoting holistic education. The implications of this research suggest that the IB framework can significantly contribute to improving EFL education by aligning teaching practices with global educational standards, thus preparing students for the complexities of an interconnected world. These insights are pivotal for educational policymakers and practitioners aiming to implement innovative and effective EFL teaching strategies.